The Impact of Nutritional Status on The Vertical Jump Perfomance Athletes - Rizki, Rizki; Sesilia, Agneta Grace; Fahlevi, Rivan Adriza; Setiawan, M.Arief; Aulia, Danny (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Volleyball is a team game played by two teams with six players in each team. It is played by volleying the ball back and forth over the net and each team tries to quickly drop the ball into the opponent's court with a perfect ball bounce. Mastery of technique, physical ability, good tactics and mentality, as well as cooperation are needed to win the game. The aim of this observation was to measure Body Mass Index (BMI) and nutrition in Sky Club volleyball athletes. This research uses a qualitative descriptive method, qualitative descriptive aims to systematically explain events that are currently occurring by emphasizing the disclosure of data based on facts obtained from the field. The results of this observation show that the Sky Club volleyball athletes have an average Body Mass Index (BMI) value in the Normal criteria. This shows that the Langit volleyball athletes do not have problems with nutrition, because they have a good diet and balanced training patterns. If it is not balanced with a programmed diet and exercise pattern, growth, in this case Body Mass Index (BMI), will be disrupted. The nutritional status of athletes at Club Langit is good, there are only a few athletes whose nutritional status is not normal, and this can all be influenced by several factors such as meal portions, lack of nutrients (carbohydrates, protein, fat, etc.) and inappropriate training. to the needs of athletes. Coaches must pay more attention to providing training progress to athletes, so that there are no more problems with nutritional status to improve the performance of Club Langit athletes. The Body Mass Index results at the Langit club were 71.47% in the Normal category and this is quite a good result. This correlates when the athletes do the vertical jump, they will be very light when doing it.